Adverse outcomes after major surgery in patients with pressure ulcer: a nationwide population-based retrospective cohort study. - Chia-Lun Chou; Woan-Ruoh Lee; Chun-Chieh Yeh; Chun-Chuan Shih; Ta-Liang Chen; Chien-Chang Liao (PLoS ONE, 2015)
Background Postoperative adverse outcomes in patients with pressure ulcer are not completely understood. This study evaluated the association between preoperative pressure ulcer and adverse events after major surgeries. Methods Using reimbursement claims from Taiwan's National Health Insurance Research Database, we conducted a nationwide retrospective cohort study of 17391 patients with preoperative pressure ulcer receiving major surgery in 2008-2010. With a propensity score matching procedure, 17391 surgical patients without pressure ulcer were selected for comparison. Eight major surgical postoperative complications and 30-day postoperative mortality were evaluated among patients with pressure ulcer of varying severity. Results Patients with preoperative pressure ulcer had significantly higher risk than controls for postoperative adverse outcomes, including septicemia, pneumonia, stroke, urinary tract infection, and acute renal failure. Surgical patients with pressure ulcer had approximately 1.83-fold risk (95% confidence interval 1.54-2.18) of 30-day postoperative mortality compared with control group. The most significant postoperative mortality was found in those with serious pressure ulcer, such as pressure ulcer with local infection, cellulitis, wound or treatment by change dressing, hospitalized care, debridement or antibiotics. Prolonged hospital or intensive care unit stay and increased medical expenditures were also associated with preoperative pressure ulcer. Conclusion This nationwide propensity score-matched retrospective cohort study showed increased postoperative complications and mortality in patients with preoperative pressure ulcer. Our findings suggest the urgency of preventing and managing preoperative pressure ulcer by a multidisciplinary medical team for this specific population.